Validity of the Early Years Check-In (EYCI) in a Cross-Sectional Sample of Families - Clark, Heather; Nair, Kalpana; Veldhuizen, Scott; Campbell, Wenonah; Rivard, Lisa; Rodriguez, M. Christine; Cairney, John (Frontiers in Pediatrics, 2020)
Background: The objective of the present study was to develop and test the validity of the Early Years Check-In (EYCI), a new tool that measures parent and educator concerns regarding children's development. The study examined the EYCI's agreement with 3rd edition of the Bayley Scales of Infant and Toddler Development (BSID-III) an established measure of child development. Two possible thresholds were explored: one to identify children with a probable delay, and another to identify children at the borderline functioning threshold. Methods: Parents of children aged 18 to 42 months were recruited from childcare settings across Ontario, Canada. The study proceeded in two phases. Phase I, intended to pilot the measure, included 49 children. Phase II, a test of the validity of the final version, included 199 children. Parents and educators completed the EYCI for the child, while a blinded assessor completed the BSID-III. Results: The EYCI demonstrated good sensitivity and specificity (86 and 82%, respectively) as a parent-completed tool that identifies children with a probable delay. However, the positive predictive value (15%) suggests the EYCI is likely to over identify children. When identifying children who demonstrated borderline delay, the EYCI demonstrated good sensitivity (80%) but poor specificity (49%). Results from educator-completed EYCIs were poor for both probable and borderline delay. Conclusions: While further research is required, the EYCI shows promise as a parent-completed tool, particularly to identify more-severe cases of delay. Results with educators were poor overall. Future research investigating accuracy of educators in different types of early childcare centres is needed.